Synthesis of the β and δ Phases of Bi2O3 Stabilized by Gd2O3 - Turkoglu, Orhan; Soylak, Mustafa (Asian Journal of Chemistry, 2010)
We report here the synthesis of bismuth trioxide polymorphs in the binary system (BiO3)1-x(Gd2O3)x( 0.01 ≤ x ≤ 0.1) by adding small amounts of Gd2O3 into pure monoclinic α-Bi2O3. We also studied on the polymorphic changes, crystallographic properties and Gd2O3 content dependence of the lattice parameters of the phases investigated. We found that minumum and maximum solubility for Gd2O3 in β-Bi2O3 are 2 and 7 mole % respectively depending on heat treatment Procedure. The δ=Bi2O3 phase could only be obtained with 9–10 mole % Gd2O3 addition.